2019
DOI: 10.1007/s10508-018-1324-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Dynamics in the Context of Binge Drinking and Polydrug Use Among Same-Sex Male Couples in Atlanta, Boston, and Chicago

Abstract: Background: An estimated one-to two-thirds of incident HIV infections among US men who have sex with men (MSM) occur within the context of a primary relationship. The existing, yet limited, literature on sexual risk behavior among same-sex couples suggests that MSM with main partners are more often to report having lower perceived HIV risk, higher unrecognized HIV infection, and increased frequency of condomless anal intercourse (CAI) with their primary partner. Furthermore, numerous studies document the stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…For at least some couples, forfeiting HIV prevention, engaging in CAS together, or stopping PrEP is interpreted as an indicator of commitment or emotional closeness [28][29][30][31]. As a result, the introduction of condom use, PrEP, or PEP to prevent HIV infection is complicated by the potential that it might convey a lack of commitment to or trust in their partner [32][33][34][35][36][37] for these couples.…”
Section: The Importance Of Ongoing Communication-why One-time Agreeme...mentioning
confidence: 99%
“…For at least some couples, forfeiting HIV prevention, engaging in CAS together, or stopping PrEP is interpreted as an indicator of commitment or emotional closeness [28][29][30][31]. As a result, the introduction of condom use, PrEP, or PEP to prevent HIV infection is complicated by the potential that it might convey a lack of commitment to or trust in their partner [32][33][34][35][36][37] for these couples.…”
Section: The Importance Of Ongoing Communication-why One-time Agreeme...mentioning
confidence: 99%
“…In their study of 260 partnered gay/bisexual men recruited in New York City, Starks et al [22] found those who did not refer their partners were older, wealthier, and in longer relationships, whereas participants who successfully recruited their partners were significantly more satisfied in their relationship. This selectivity is important to consider in light of evidence illustrating associations between poor relationship characteristics and HIV prevention outcomes [3,5,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%